Affix In Sentence Pattern of Indonesia-Makassarese Dialect - Ansar, Fithrah Auliya (Universitas Islam Negeri Raden Intan Lampung, 2016)
Language in every reagon has some diversities. It turns into dialect for every culture which consumes the national language. In south sulawesi, the people use Indonesia with a special dialect as a characteristic of the people there. The national language, Indonesia, use as common as other region but there are specific differences in its affix in South Sulawesi. In Morphology, Affix is a part of word which has a special meaning. It is a kind of bound morphem. In makassarese there are several suffixes which have some meaning. The objective of this research is to describe the meaning of each suffix in terms of sequence of its grammatical function. Then too see how the affixes work in sentence pattern of Indonesia-Makasarese dialect. The method used in this research is descriptive- qualitative. The analysis used is Morphosyntaxis. It is focused on explaining the grammatical function in the use of Indonesian-Makassarese dialect. The analysis shows that, the writer explained a lot of about basic sentence pattern from Indonesian Language with Makassarese dialect, from which the writer get similarities on the element of the sentence formation, such as : subject (S), predicate (P or V), and object (O) in a sentence. The sentence pattern S+ V in English is similar to Indonesian-Makassarese dialect sentence pattern; But Indonesian-Makassarese dialect have special affixes which have special class as KB or noun, (KS) or adjective, ( KK) or verb and (Kata ganti orang) or Personal pronoun. Indonesia and Indonesia-makassarese dialect have some similarities in structure of type such as S+P or S+V and S+P+O or S+V+O. Furthermore, the difference between the basic sentence in Indonesia and Indonesia-Makassarese dialect are the element sentence formations. In Indonesia-Makassarese dialect sentence pattern are S+V+O, this patterns flexible. It can change into V+S+O, V+O+S and V+S without changing its meaning. While in Indonesia, sentence pattern is a permanent, it does not change pattern.